Characterization of Calmodulin–Fas Death Domain Interaction: An Integrated Experimental and Computational Study - Fancy, Romone M. (American Chemical Society, 2014)
[Image: see text] The Fas death receptor-activated death-inducing signaling complex (DISC) regulates apoptosis in many normal and cancer cells. Qualitative biochemical experiments demonstrate that calmodulin (CaM) binds to the death domain of Fas. The interaction between CaM and Fas regulates Fas-mediated DISC formation. A quantitative understanding of the interaction between CaM and Fas is important for the optimal design of antagonists for CaM or Fas to regulate the CaM–Fas interaction, thus modulating Fas-mediated DISC formation and apoptosis. The V254N mutation of the Fas death domain (Fas DD) is analogous to an identified mutant allele of Fas in lpr-cg mice that have a deficiency in Fas-mediated apoptosis. In this study, the interactions of CaM with the Fas DD wild type (Fas DD WT) and with the Fas DD V254N mutant were characterized using isothermal titration calorimetry (ITC), circular dichroism spectroscopy (CD), and molecular dynamics (MD) simulations. ITC results reveal an endothermic binding characteristic and an entropy-driven interaction of CaM with Fas DD WT or with Fas DD V254N. The Fas DD V254N mutation decreased the association constant (K(a)) for CaM–Fas DD binding from (1.79 ± 0.20) × 10(6) to (0.88 ± 0.14) × 10(6) M(–1) and slightly increased a standard state Gibbs free energy (ΔG°) for CaM–Fas DD binding from −8.87 ± 0.07 to −8.43 ± 0.10 kcal/mol. CD secondary structure analysis and MD simulation results did not show significant secondary structural changes of the Fas DD caused by the V254N mutation. The conformational and dynamical motion analyses, the analyses of hydrogen bond formation within the CaM binding region, the contact numbers of each residue, and the electrostatic potential for the CaM binding region based on MD simulations demonstrated changes caused by the Fas DD V254N mutation. These changes caused by the Fas DD V254N mutation could affect the van der Waals interactions and electrostatic interactions between CaM and Fas DD, thereby affecting CaM–Fas DD interactions. Results from this study characterize CaM–Fas DD interactions in a quantitative way, providing structural and thermodynamic evidence of the role of the Fas DD V254N mutation in the CaM–Fas DD interaction. Furthermore, the results could help to identify novel strategies for regulating CaM–Fas DD interactions and Fas DD conformation and thus to modulate Fas-mediated DISC formation and thus Fas-mediated apoptosis.